14C Ages of the Last Eruptive Stage of Faial Island Caldeira Volcano. Issue 5 (2015) - Pacheco, J M
Abstract : Faial is one of the nine islands that form the Azores archipelago in the North Atlantic, characterized by a complex geodynamic setting dominated by the triple point where the North American, Eurasian, and African lithospheric plates meet (Figure 1).